Distance Education and Teacher Formation: by a Possible Didactics - Lima, Daniela da Costa Britto Pereira (2017)
Abstract: this article aims to present the results of the research carried out with the objective of analyzing distance education (DE) and the need for a new didactic in virtual learning environments. In bibliographical and documentary research, the focus was on theorists as Peters (2001), Feenberg (2004), Toschi (2005a, 2005b, 2013), among others, and on the legislation governing this modality of teaching. The text concludes with considerations about didactics in DE and the importance of teacher mediation in virtual learning environments and that in teacher formation digital technologies are understood as a mediated action in a didactic perspective that surpasses the instrumental model. Educação a distância e formação do professor: por uma didática possível Resumo: este artigo tem como objetivo apresentar resultados da pesquisa realizada com o objetivo de analisar a educação a distância (EaD) e a necessidade de uma nova didática nos ambientes virtuais de aprendizagem (AVA). Na pesquisa bibliográfica e documental, o foco recaiu sobre teóricos como Peters (2001), Feenberg (2004), Toschi (2005a, 2005b, 2013), entre outros, e sobre a legislação que rege essa modalidade de ensino. Conclui-se o texto com considerações acerca da didática na EaD e da importância da mediação docente nos AVA e de que na formação de professores as tecnologias digitais sejam compreendidas como uma ação mediatizada numa perspectiva didática que supera o modelo instrumental.